The Legal Concept of Rehabilitation for Military Narcotics Offenders: A Comparative Analysis and Assurance of Legal Certainty - Abdul Salam; Agus Surono; Mulyono Mulyono (IJOSPOL - International Journal of Social, Policy and Law, 2026)
On the other hand, national laws such as the Narcotics Law and the Health Law emphasize that addicts are individuals suffering from an illness and therefore must undergo rehabilitation. The inconsistency between health-based approaches and the military legal system creates regulatory disharmony, legal uncertainty, and the loss of rehabilitation rights for military personnel who use narcotics. This study aims to analyze the legal concept of rehabilitation for military personnel, assess regulatory consistency based on the principles of legal certainty and the right to health, compare international practices, and formulate an ideal model applicable within Indonesia’s military legal system.This research employs a normative juridical approach to examine applicable legal norms, a case approach to review military court practices, a comparative approach focusing on the policies of Portugal, Switzerland, Malaysia, and Thailand, and lingual triangulation to ensure consistency between legal and medical terminology. The findings show that four core military regulations the TNI Law, the Military Court Law, the Military Penal Code (KUHPM), and the Military Discipline Law do not regulate rehabilitation, resulting in a normative vacuum and disharmony with the Narcotics Law and the Health Law. The absence of rehabilitation SOPs causes military narcotics users to be treated similarly to criminal offenders and often punished without medical assessment, which contradicts the principles of justice, the right to health, and the principle of equality before the law. Comparative studies indicate that countries separating users from traffickers and implementing integrated rehabilitation systems have successfully reduced relapse rates and increased the effectiveness of narcotics policies.The study concludes that rehabilitation for TNI personnel is a legal, medical, and institutional necessity to ensure legal certainty, justice, and the protection of health rights. This research recommends harmonizing regulations between military law and health–narcotics law, establishing an Integrated TNI Rehabilitation Service, mandating medical assessments prior to sanctioning, and applying a blended sentencing model as the ideal concept for handling military personnel who use narcotics.